The use of bioindication to determine the possibility of sludge recovery after biological treatment of wastewater - Shkvirko, Oksana; Tymchuk, Ivan; Malovanyy, Myroslav (Lviv Politechnic Publishing House, 2018)
These studies were conducted to test the hypothesis that sewage sludge from Lviv municipal wastewater treatment plants (LMWWTP) facilities can be used to create a substrate that can be used for biological reclamation. The qualitative composition of sewage sludge from Lviv municipal wastewater treatment plants is determined. The study of bioindication of a mixture of sludge with dark gray soil was carried out in two stages, which showed a significant difference between fresh and settled sludge. Possible conditions for the use of sludge in the substrate are presented.
Keywords: sewage sludge; substrate; LMWWTPs; bioindication; spent active sludge